Alcohol Screening and Brief Intervention in Workplace Settings and Social Services: A Comparison of Literature - Schulte, Bernd; O’Donnell, Amy Jane; Kastner, Sinja; Schmidt, Christiane Sybille; Schäfer, Ingo; Reimer, Jens (Frontiers in Psychiatry, 2014)
BACKGROUND: The robust evidence base for the effectiveness of alcohol screening and brief interventions (ASBI) in primary health care (PHC) suggests a widespread expansion of ASBI in non-medical settings could be beneficial. Social service and criminal justice settings work frequently with persons with alcohol use disorders, and workplace settings can be an appropriate setting for the implementation of alcohol prevention programs, as a considerable part of their social interactions take place in this context. METHODS: Update of two systematic reviews on ASBI effectiveness in workplaces, social service and criminal justice settings. Review to identify implementation barriers and facilitators and future research needs of ASBI in nonmedical settings. RESULTS: We found a limited number of randomized controlled trials (RCTs) in non-medical settings with an equivocal evidence of effectiveness of ASBI. In terms of barriers and facilitators to implementation, the heterogeneity of non-medical settings makes it challenging to draw overarching conclusions. In the workplace, employee concerns with regard to the consequences of self-disclosure appear to be key. For social services, the complexity of certain client needs suggest a stepped and carefully tailored approach is likely to be required. DISCUSSION: Compared to PHC, the reviewed settings are far more heterogeneous in terms of client groups, external conditions and the focus on substance use disorders. Thus, future research should try to systematize these differences, and consider their implications for the deliverability, acceptance and potential effectiveness of ASBI for different target groups, organisational frameworks and professionals.